High yield ultrasonication extraction method for Undaria pinnatifida sporophyll and its anti-inflammatory properties associated with AP-1 pathway suppression. Issue 2 (December 2015) - Song, Kyung-Mo; Ha, Su Jong; Lee, Jang-Eun; Kim, Soon-Hee; Kim, Yong Ho; Kim, Youngeon; Hong, Sang Pil; Jung, Sung Keun; Lee, Nam Hyouck
Abstract Developing efficient and eco-friendly extraction methods is a major goal of the functional food industry. We developed an ultrasonication extraction method for Undaria pinnatifida sporophyll requiring 6 h extraction time at 80% amplitude. This application of ultrasonication increases yield by 25% and decreases extraction time by approximately 18 h. Additionally, we investigated the effect of the ultrasonicated sporophyll from Undaria pinnatifida extract (UPE) on LPS-induced inflammation. Following ultrasonication, the average molecular weight decreases in comparison to conventional methods, in a similar manner to commercial fucoidan. UPE significantly suppresses lipopolysaccharide (LPS)-induced nitrite and PGE2 production and subsequently suppresses inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2 expression in Raw 264.7 cells. Western blot assay results also demonstrate that UPE strongly suppresses LPS-induced c-Jun N terminal kinase (JNK) 1/2/MKK 4 and p38/MKK3/6 phosphorylation in Raw 264.7 cells. SR11302, an AP-1 specific inhibitor, suppressed LPS-induced iNOS and COX-2 expression. In addition, SiMLK3 strongly suppressed LPS-induced iNOS and COX-2 expression, as well as JNK1/2 and p38 phosphorylation in Raw 264.7 cells. Taken together, these results suggest that this ultrasonication extraction method is more efficient for extracting sporophyll of Undaria pinnatifida extract, which has potent anti-inflammatory properties.